Kedudukan Perempuan dalam Hukum Keluarga Islam Di Indonesia (Telaah Kompilasi Hukum Islam Perspektif Kesetaraan Gender) - Asni Asni (Institut Agama Islam Negeri (IAIN) Kendari, 2008)
This research is motivated by the rise of gender discourse in the last two decades as a reaction to the reality of gender imbalances that have given birth to injustice to women in the form of marginalization, subordination, and violence against women which has also occurred in the family. The existing discourse among others voiced the importance of renewing the various rules of law that are considered gender biased.This study aims to reveal the position of women in family law through a study of the rules contained in the Compilation of Islamic Law as an applied law for the Religious Courts within the framework of gender equality perspectives.The study of the article by article relating to gender relations in the rules of family life, it appears that although some of these rules still have certain parts that seem biased gender, generally it can be concluded that KHI enough to show equality between men and women in family life. Gender equality perspectives include among others the rules on equality of positions of husbands and wives, restrictions on polygamy, common property, divorce, divorce, child domination and inheritance